The Design and Manufacture of the Neutral Beam Injection Thermal Shield for the EAST Tokamak. (1st November 2016) - Liu, Changle; Yao, Damao; Li, Lei; Zhang, Jie; Yang, Hao; Qiu, Yang; Gao, Xiang
Abstract: Neutral beam injection (NBI) is a high-power auxiliary heating system for the EAST device. We present a thermal shield (TS) structure to protect the neck pipe of the EAST equatorial port to avoid damage from the NBI beam. Since the EAST port has a big trumpet structure, a straight section, and a small trumpet structure, to accommodate the port structure, a TS concept is put forward including its cooling system. The cooling loops and the sub-branches were designed with interfaces between the inner cooling branches. The heat removal capability is verified by a thermal hydraulics analysis based on ANSYS code. In particular, fabrication is addressed with technical processing technology, especially for the embedded cooling pipes in the heat sinks. The pipes are checked for leaks after bending and the embedding processing. The assembly activities are demonstrated in the spatial space zones of the port before the engineering installation. It is confirmed that the TS structure is safe and will run feasibly in the EAST discharge. It is indicated that the TS structure can provide thermal shielding and remove heat for the NBI device in the port region.